Implementasi Pembelajaran Daring Dan Luring Pada Mata Pelajaran Geografi SMA Di Kabupaten Morowali - Amria; Nurvita (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2021)
This study aims to describe the preparation of online and luring learning carried out by teachers, students and parents, the implementation of learning, learning evaluation, constraints experienced by students and teachers in the study of learning, and what efforts of teachers do for the achievement of online learning and luring which is good especially in high school geographic subjects in Morowali district. This research was conducted at Pongku 1 Public High School and 2 Pongku State High School, Central Bungku District, Morowali Regency. The type of qualitative descriptive research that uses samples of teachers and students of class X IPS in SMA 1 Pongku and 2 Pongku State High School, and parents of students. Data collection using observation, interviews and documentation methods. The results showed that learning planning needed to be prepared before starting online and luring learning such as preparing internet quota or wifi network that could support learning, preparing teaching materials, learning videos, ppt, and tasks to be distributed to students. The implementation of online and luring learning uses several learning support applications such as WhatssApp, Quipper, Zoom, and Classroom, the teacher also sends learning animated videos and ppt to support online learning, in learning teachers coming to students to be given learning materials and tasks. Constraints in learning experienced by teachers and students at access to internet networks, submission/material receipts, the high cost of data packages. In Luring Learning Kenda is the distance of the house and the school is quite far enough to make it difficult for teachers to come to their respective students.